Screening method for diabetic retinopathy: a review / Ani Zahidah Yahya - Yahya, Ani Zahidah (Faculty of Health Sciences, 2015)
Screening for diabetic retinopathy can be successful with collaboration of all health care providers and government in supporting the screening programme. Screening can reduce and halt blindness and visual impairment resulted from late diagnosis of diabetic retinopathy. This paper systemically reviews the published literature on the screening methods for diabetic retinopathy itself. Searches were done through online database of UiTM library until May 2015. 13 studies fulfilled the inclusion criteria as these assessed the screening modalities used in all over the world. Mydriatic retinal photograph and slit lamp biomicroscopy is the promising approach in screening for the diabetic retinopathy. Nonetheless of the limitations of nonmydriatic retinal photograph, it is being accepted in few countries such as Scotland national screening programme. Implications of the study will expose Malaysia to various screening strategies being used in the world and specifically deliberates on screening battery that can be used in UiTM Optometry clinic in near future. Good screening strategy for diabetic retinopathy detection will lessen visual impairments resulting from late referrals to opthalmology departments to get treatment.